PERAN MOTIVASI BELAJAR SEBAGAI MODERASI ANTARA GAYA MENGAJAR GURU DAN FASILITAS BELAJAR TERHADAP HASIL BELAJAR KOMPUTER AKUNTANSI DI SMK SWASTA KECAMATAN PULOGADUNG JAKARTA TIMUR - Eliza, Elin; Zulaihati, Sri; Mardi, Mardi (JURNAL RISET PENDIDIKAN DAN PENGAJARAN, 2023)
This study examines how learning motivation affects the relationship between teacher teaching style and learning facilities on computer accounting learning outcomes in Private Vocational High Schools (SMK) in Pulogadung District. 89 students from four randomly selected private vocational schools participated in the study. Teacher teaching style was measured using a questionnaire focusing on interactivity and teacher involvement. Learning facilities were assessed based on availability and infrastructure. Student's learning motivation was measured using a scale of intrinsic and extrinsic motivation. Data collection techniques included tests, questionnaires, and documentation. Various techniques, such as validity and reliability tests, multiple linear regression, hypothesis testing, and moderation tests, were used to analyze the data. The results showed that teacher teaching style positively influenced learning outcomes, while learning facilities did not have a significant effect. Learning motivation moderated the relationship between teacher teaching style and learning outcomes, but not between learning facilities and learning outcomes. Overall, both teachers teaching style and learning facilities had a simultaneous influence on computer accounting learning outcomes.